Camel Urine for Health in Islam and Science Perspective - Wachidah Nur Latifah; Siti Nur Ngaeni; Rian Adi Setia Rahman; Inarotu Millati Azka; Mohammad Ali Maqshudi Zaen (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2018)
This research is aimed to determine the benefits of urine and milk’s camel as a medicine, anti-bacterial, and anti-fungial. It is related with hadith of Prophet Muhammad, Peace upon on Him (puh) about the benefits of milk and urine’s camel. Camel urine is used as an alternative medicine for Middle Eastern societies. But there is controversy in consuming camel urine especially for some people whose think that camel urine as a najis. The result from in vitro laboratory has proved that camel urine as an inhibitor of cancer cells, anti-bacterial, and anti-fungal. Until now yet research found on health tests for people who routinely consume camel urine. In addition, there have not been many studies in vivo. Based on the study side of fiqh, Shafi'i and Hanafi school of thought (madzhab) regard camel urine so najis that it should not be consumed. Meanwhile according to the Hanbali of school of thought (madzhab) the camel urine is not najis because the camel is a halal animal eaten, while the Maliki school of thought (madzhab) has the same opinion with the Hanbali school of thought (madzhab) but if the animal consumes something that is najis then the law of dirt and urine becomes najis.